Nilai-nilai Sosial-Religius dalam Tradisi Meron di Masyarakat Gunung Kendeng Kabupaten Pati - Imam Subqi (Institut Agama Islam Negeri Jember, 2020)
Abstract This research aims to describe the meron tradition in mount kendeng community at Pati Regency and to address the socio-religious values reflected in the meron tradition. The research used qualitative approach, and the data collection techniques were done through interviews, observation and documentation. The data were analysed through interactive models and validated through triangulation technique. The findings of the study show that the tradition of meron in javanese perspective is considered a form of public gratitude to the God Almighty, for the abundance of sustenance that has been given. On the other hand, the tradition of meron is carried out to commemorate the birth of the Prophet Muhammad SAW. Meron become the embodiment of Javanese and Islamic cultural acculturation. In the tradition of meron, there are ritual, prayer and magical activities performed accompanied by gamelan, terbangan and other traditional arts. Social values reflected in the meron tradition are compassion, living together, togetherness/solidarity, and responsibility. Religious values reflected in the meron tradition include the value of worship, love for the Prophet Muhammad, gratitude, the value of trust, and exemplary. Abstrak Penelitian ini bertujuan untuk mendeskripsikan tradisi meron masyarakat gunung Kendeng di Kabupaten Pati dan menyibak nilai-nilai sosial-religius yang tercermin dalam tradisi meron tersebut. Pendekatan penelitian menggunakan kualitatif, teknik pengumpulan data menggunakan wawancara, observasi partisipan dan dokumentasi. Analisis data menggunakan model interaktif dan keabsahan data dilakukan dengan triangulasi. Temuan penelitian menunjukkan bahwa tradisi meron dalam perspektif jawa dianggap sebagai wujud syukur masyarakat kepada yang Maha Kuasa atas limpahan rezeki yang telah diberikan. Disisi lain tradisi meron dilakukan untuk memperingati kelahiran Nabi Muhammad SAW. Meron menjadi perwujudan akulturasi budaya Jawa dan Islam. Dalam tradisi meron ada kegiatan ritual, doa selametan dan magis yang dilakukan dengan diiringi gamelan, terbangan dan kesenian tradisional lainnya. Nilai sosial yang tercermin dalam tradisi meron yaitu kasih sayang, hidup rukun, kebersamaan/solidaritas, dan tanggung jawab. Nilai religius dalam tradisi meron meliputi nilai ibadah, kecintaaan pada Nabi Muhammad SAW, syukur, nilai amanah, dan keteladanan. Kata Kunci: nilai sosial, nilai religius dan tradisi meron